Evaluation of a novel assay for detection of the fetal marker RASSF1A: facilitating improved diagnostic reliability of noninvasive prenatal diagnosis. - Helen E White; Carolyn L Dent; Victoria J Hall; John A Crolla; Lyn S Chitty (PLoS ONE)
Background Analysis of cell free fetal (cff) DNA in maternal plasma is used routinely for non invasive prenatal diagnosis (NIPD) of fetal sex determination, fetal rhesus D status and some single gene disorders. True positive results rely on detection of the fetal target being analysed. No amplification of the target may be interpreted either as a true negative result or a false negative result due to the absence or very low levels of cffDNA. The hypermethylated RASSF1A promoter has been reported as a universal fetal marker to confirm the presence of cffDNA. Using methylation-sensitive restriction enzymes hypomethylated maternal sequences are digested leaving hypermethylated fetal sequences detectable. Complete digestion of maternal sequences is required to eliminate false positive results. Methods cfDNA was extracted from maternal plasma (n = 90) and digested with methylation-sensitive and insensitive restriction enzymes. Analysis of RASSF1A, SRY and DYS14 was performed by real-time PCR. Results Hypermethylated RASSF1A was amplified for 79 samples (88%) indicating the presence of cffDNA. SRY real time PCR results and fetal sex at delivery were 100% accurate. Eleven samples (12%) had no detectable hypermethylated RASSF1A and 10 of these (91%) had gestational ages less than 7 weeks 2 days. Six of these samples were male at delivery, five had inconclusive results for SRY analysis and one sample had no amplifiable SRY. Conclusion Use of this assay for the detection of hypermethylated RASSF1A as a universal fetal marker has the potential to improve the diagnostic reliability of NIPD for fetal sex determination and single gene disorders.